The Duality of Persistence: Academic Enclaves and International Students’ Aspirations to Stay in the U.S. - Kaul, Vasundhara; Renzulli, Linda (Journal of International Students, 2021)
International students have been a growing presence in U.S. higher education institutions for over a decade. Feelings of belonging play a crucial role in the adjustment of these students to campus life in American universities, and their conationals play a significant role in facilitating this adjustment process. However, the role of belonging and co-national communities in facilitating the persistence of international students toward and beyond degree attainment remains understudied. In our examination of the aspirations of 642 international students across 9 U.S. universities, we establish that stronger feelings of academic and social belonging are associated with a higher likelihood of aspiring to stay in the United States after graduation. In particular, we demonstrate the presence of an academic enclave effect wherein larger communities of co-nationals have a stronger influence on the aspirations of international students with low social belonging but does not affect the aspirations of socially well-integrated international students.